October ogre - Roy, Ron, 1940-; Gurney, John Steven, 1962- (New York : Random House, 2013)
Bradley, Brian, Nate, and Lucy visit a haunted hotel on Halloween, but once inside they realize that they have seen plenty of people going in and none coming back out.
"A Stepping Stone book."
"With the younger siblings of the A to Z mysteries kids!"--Cover.
RL: 2.2.
006-009.
Accelerated Reader
Keywords: Detective and mystery stories; Haunted houses -- Juvenile fiction; Halloween -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters -- Juvenile fiction; Cousins -- Juvenile fiction; Mystery and detective stories; Haunted houses -- Fiction; Halloween -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Cousins -- Fiction; Brothers and sisters -- Juvenile fiction; Cousins -- Juvenile fiction; Detective and mystery stories; Halloween -- Juvenile fiction; Haunted houses -- Juvenile fiction; Twins -- Juvenile fiction; Brothers and sisters; Cousins; Detective and mystery stories; Halloween; Haunted houses; Twins; Cousins -- Fiction; Halloween -- Fiction; Brothers and sisters -- Juvenile fiction; Cousins -- Juvenile fiction; Halloween -- Juvenile fiction; Haunted houses -- Juvenile fiction; Mystery fiction; Twins -- Juvenile fiction; Detective and mystery fiction; Fiction; Juvenile works; Mystery fiction; Detective and mystery fiction